Pengaruh Waktu Perendaman Terhadap Uji Kuat Tekan Paving Block Dengan Campuran Tanah, Pasir Dan Semen Menggunakan Alat Pemadat Modifikasi - Agusni, Restu; Setyanto, Setyanto; Iswan, Iswan (Universitas Lampung, 2017)
Paving blocks are compositions of building material constructed from a mixture of Portland cement or other similar hydrolysis, water, and aggregate with or without other additives which do not reduce the quality of the material. Paving blocks in the field are made of cement, sand, aggregate, and water by mixing all the ingredients and form the paving blocks. In this research, the paving blocks are made of the mixture of soil, sand, and cement. In the process, the paving blocks are compacted by a modified penetration tool in order to improve the paving blocks quality in accordance with SNI-03-0691-1996.The soil samples used in this research were from Kota Baru, Lampung Selatan. The amount of mixture used for making the paving block was 75% of soil, 10% of sand and 15% of cement. The variations of curing time were 7 days, 14 days, 21 days and 28 days as well as with pre and post burning treatment on the paving block samples.The results of the compressive strength test to the paving blocks which are made of soil, sand, and cement showed that the cement and sand do not meet the standard of SNI 03-0691-1996 for the paving block classification because the highest compressive strength value is obtained by the paving blocks with pre and post burning treatment on the variation mixture of 75% soil, 10% sand, and 15% cement with the value 7,65 MPa and 7,25 MPa. The result of water absorption value which was between 16,6% - 25,4% do not meet the specification in SNI-03-0691-1996.Keywords: Paving block, silt, compressive strength, water absorption